2007
DOI: 10.1007/s10709-007-9158-1
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic clonal lineages and genetic diversity in the loach Misgurnus anguillicaudatus (Teleostei: Cobitidae) inferred from nuclear and mitochondrial DNA analyses

Abstract: In the loach Misgurnus anguillicaudatus, the asexual lineage, which produces unreduced clonal diploid eggs, has been identified. Among 833 specimens collected from 54 localities in Japan and two localities in China, 82 candidates of other lineage(s) of cryptic clones were screened by examining RFLP (restriction fragment length polymorphism)-PCR haplotypes in the control region of mtDNA. This analysis was performed because triploid loaches arise from the accidental incorporation of the sperm nucleus into unredu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
109
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 82 publications
(118 citation statements)
references
References 45 publications
8
109
0
1
Order By: Relevance
“…In wild populations of Japan, most individuals are bisexually reproducing diploid with 2n = 50 chromosomes, but a small number of gynogenetically reproducing clonal diploid individuals have been detected in a few localities by experimental reproduction and molecular genetic analyses (Morishima et al 2002(Morishima et al , 2008. The occurrence of natural triploid and diploid-triploid mosaic individuals has also been recorded at low frequencies in a few localities in Japan (Zhang and Arai 1999;Arai 2003;Morishima et al 2004;Yoshikawa et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In wild populations of Japan, most individuals are bisexually reproducing diploid with 2n = 50 chromosomes, but a small number of gynogenetically reproducing clonal diploid individuals have been detected in a few localities by experimental reproduction and molecular genetic analyses (Morishima et al 2002(Morishima et al , 2008. The occurrence of natural triploid and diploid-triploid mosaic individuals has also been recorded at low frequencies in a few localities in Japan (Zhang and Arai 1999;Arai 2003;Morishima et al 2004;Yoshikawa et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of natural triploid and diploid-triploid mosaic individuals has also been recorded at low frequencies in a few localities in Japan (Zhang and Arai 1999;Arai 2003;Morishima et al 2004;Yoshikawa et al 2007). Although no natural tetraploid individuals have been discovered in wild populations of Japan even after long-term intensive screening with DNA content flow cytometry (Zhang and Arai 1999;Arai 2003;Morishima et al 2008), bisexually reproducing tetraploid loaches (4n = 100) have been found among market samples in Japan but their exact origin has not been identified yet (Ojima and Takai 1979;Zhang and Arai 1999;Arai et al 1991a). These tetraploid individuals were reported to form diploid gametes and hybrids between tetraploid and diploid were triploid with 3n = 75 chromosomes (Arai et al 1991a(Arai et al , b, 1993Zhang and Arai 1996).…”
Section: Introductionmentioning
confidence: 99%
“…However, analyses of the sequences of the mtDNA control region clearly indicated the presence of two different clades, probably corresponding to two species in the phylogenic tree. This strongly suggests that Japanese M. anguillicaudatus might be comprised of at least two cryptic species (Morishima et al, 2008a). Currently, the evolutionary status of the clonal loach remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Sampel tersebut kemudian disimpan dalam larutan alkohol 70% untuk selanjutnya dapat dianalisis genotipe dengan metode PCR-RAPD dengan mengacu pada Gustiano et al (2016). Primer yang digunakan yaitu OPA-12, OPC-04, dan OPC-06 setelah dilakukan seleksi pada delapan primer yaitu OPA-07, OPA-11, OPA-12 (Morishima et al, 2008), OPC-01, OPC-02, OPC-04, OPC-05, dan OPC-06 (Alam & Khan, 2001). …”
Section: Karakterisasi Genotipeunclassified